Fundamentals of investments valuation and management - Corrado, Charles J.; Jordan, Bradford D. (The Irwin/McGraw-Hill series in finance, insurance, and real estate, 2015)
Focuses on students as investment managers, giving them information to act on by placing theory and research in the proper context. This book offers a balanced, unified treatment of the four main types of financial investments-stocks, bonds, options, and futures